TRANSFORMATIVE LEADERSHIP IN THE DIGITAL ERA: A SYSTEMATIC ANALYSIS OF SOCIAL IMPLICATIONS FOR FUTURE-READY ORGANIZATIONS - Delfi, Asri; Yunianto, Eko; Sariyono, Eko Budi; Sukandar; Humokor, Edwin Johanis; Simbolon, Octorolas; Astuti, Dwi (Ikatan Dosen Menulis, 2024)
This research examines the evolving nature of transformative leadership in digitally transformed organizations through a systematic analysis of scholarly literature from 2004 to 2024. While digital transformation has fundamentally altered organizational landscapes, existing leadership frameworks often fail to address the complex interplay between technological innovation, regulatory compliance, and social responsibility. Through a comprehensive analysis of publications indexed in the Scopus database, this study identifies three distinct phases in the evolution of leadership paradigms: Traditional Leadership (2004-2012), Digital Transition (2013-2019), and Integrated Leadership (2020-2024). The research introduces the